A targeting method for robot-assisted percutaneous needle placement under fluoroscopy guidance. (1st October 2019) - Han, Zhonghao; Yu, Keyi; Hu, Lei; Li, Weishi; Yang, Huilin; Gan, Minfeng; Guo, Na; Yang, Biao; Liu, Hongsheng; Wang, Yuhan
Abstract: Minimally invasive procedures are rapidly growing in popularity thanks to advancements in medical robots, visual navigation and space registration techniques. This paper presents a precise and efficient targeting method for robot-assisted percutaneous needle placement under C-arm fluoroscopy. In this method, a special end-effector was constructed to perform fluoroscopy calibration and robot to image-space registration simultaneously. In addition, formulations were given to compute the movement of robot targeting and evaluate targeting accuracy using only one X-ray image. With these techniques, radiation exposure and operation time were reduced significantly compared to other commonly used methods. A pre-clinical experiment showed that the maximum angle error was 0.94° and the maximum position error of a target located 80mm below the end-effector was 1.31mm. And evaluation of the system in a robot-assisted pedicle screws placement surgery has justified the accuracy and reliability of proposed method in clinical applications.